Surfactant Enhanced Drying of Water based Polymeric Coatings - Daisy, Sharma (My University, 2017)
Coatings of poly(vinyl alcohol)-water based system have been studied. Different types of ionic, non ionic and fluoro based surfactants were used. The effect of surfactant on drying behavior of coatings was studied. Ionic surfactant could not change the drying mechanism of the coatings. Whereas in non ionic surfactant changed to the drying behavior to a small extent. The significant change was observed in fluoro based surfactant. The drying rate in fluoro based surfactant was moderate for a longer time which then caused the more solvent recovery. Different solution of polymer concentration needs different amount of surfactant for significant change in drying behavior.
Keywords: Waterbased coatings; Surfactant enhanced drying; Thin films; Polymeric coatings